Pengaruh Pembelajaran Pendidikan Agama Islam terhadap Karakter Religius Siswa Sekolah Menengah Kejuruan - Ernawati, Yuni; Saputro, Anip Dwi; Syam, Aldo Redho (Jurnal Pendidikan Nusantara, 2024)
The purpose of this study was to determine the influence and how much influence Islamic religious education has on students' religious character. The research method used is quantitative research. And for data collection used are observation, questionnaires, and documentation. The analysis used is simple linear regression analysis using the SPSS 20.0 application to determine the results of the research data that has been carried out. The results of the study can be concluded with data processing stating that there is a significant influence between Islamic religious education learning on the religious character of class XI students of SMK Muhammadiyah 1 Ponorogo by 37.6% on students' religious character and the rest is influenced by other factors not included in this study.